Characterization of Simulated Postconsumer Recycled Poly (Lactic Acid) (Pla): Evaluation of Reprocessing Cycles on Its Physicochemical Properties - Guarda-Moraga, A; Rodriguez-Mercado, F; Bruna-Bugueno, J; Romero-Figueroa, J; Galotto-Lopez, M; Torres-Mediano, A (John Wiley and Sons Inc, 2025)
This study aims to investigate the behavior of poly (lactic acid) (PLA) by simulating its post-consumption use and mechanical recycling through multiple extrusion processes. Due to PLA being used in the production of packaging materials for beverages such as water and juice, the plastic was exposed to food simulants A and B according to international regulatory standards, and these materials were then subjected to repeated extrusion cycles, with a maximum of five cycles. After each cycle, the material s properties were evaluated through physicochemical characterization, including determination of the mean molecular weight by viscosity (Mv), melt flow index (MFI), structural analysis via infrared spectroscopy (FTIR), IZOD impact strength, thermal behavior using differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA), and color evaluation using the CIELAB scale. Although a change in the molecular weight of the PLA samples was observed after different initial treatments and reprocessing, these did not significantly affect the thermal and mechanical properties of the materials. However, a noticeable color change occurred after the reprocessing cycles. This would indicate polyester degradation through various mechanisms and the generation of chromophore species. © 2025 Wiley Periodicals LLC.